Students' perception of Kahoot!'s influence on teaching and learning - Sherlock A. Licorish; Helen E. Owen; Ben Daniel; Jade Li George (The Asia-Pacific Society for Computers in Education (APSCE), 2018)
Abstract Technology is being increasingly integrated into teaching environments in view of enhancing students' engagement and motivation. In particular, game-based student response systems have been found to foster students' engagement, enhance classroom dynamics and improve overall students' learning experience. This article presents outcomes of research that examined students' experience using a game-based student response system, Kahoot!, in an Information Systems Strategy and Governance course at a research-intensive teaching university in New Zealand. We conducted semi-structured interviews with students to learn about the extent to which Kahoot! influence classroom dynamics, motivation and students' learning process. Key findings revealed that Kahoot! enriched the quality of student learning in the classroom, with the highest influence reported on classroom dynamics, engagement, motivation and improved learning experience. Our findings also suggest that the use of educational games in the classroom is likely to minimise distractions, thereby improving the quality of teaching and learning beyond what is provided in conventional classrooms. Other factors that contributed to students' enhanced learning included the creation and integration of appropriate content in Kahoot!, providing students with timely feedback, and game-play (gamification) strategies.